Fatigue limit evaluation of various martensitic stainless steels with new robust thermographic data analysis. (May 2015) - De Finis, R.; Palumbo, D.; Ancona, F.; Galietti, U.
Highlights: Assessing the fatigue limit in automatable way by means of thermographic technique. New procedure for processing of thermal data. Study of fatigue behavior of martensitic and precipitation hardening steels. Abstract: Thermography represents an important tool to study fatigue behaviour of materials. In this work, the fatigue limit of martensitic and precipitation hardening stainless steels has been determined with thermographic methods. Despite their use in corrosive and cryogenic environments, there is a data lack in literature concerning the study of fatigue behaviour. The peculiarity of these materials is the brittle behaviour: therefore, during fatigue tests the characteristic small deformations determine small changes of temperature. Thus, to properly determine the fatigue limit of aforementioned stainless steels, a more accurate setup is necessary in order to correctly detect surface temperature of specimens due to dissipation heat sources. In literature, different procedures have already been proposed to evaluate the fatigue limit from thermal data but very few works lead to an early detection of dissipation process which can obtain a further reduction of overall testing time. The aim of the paper is to propose a new robust thermal data analysis procedure for estimating fatigue limit of stainless steels in automatable way.